Relationship Between Quality of Life and Disease Severity in Patients with Psoriasis - Kobra Soltandehghan; Tahereh Najafi-Ghezeljeh (Tehran University of Medical Sciences, 2017)
Background & Aim: Besides the disease severity of Psoriasis, the quality of life is highly important; however, the relationship between the two is not clear. This study was carried out with the aim of determining the relationship between the quality of life and disease severity in patients with psoriasis. Methods & Materials: ‎This cross-sectional study was conducted on 99 patients with psoriasis who referred to Razi hospital, Tehran University of Medical Sciences, Tehran, Iran in 2015. The patients who met the inclusion criteria of the study were recruited by convenience sampling. The data was collected, using Dermatology Quality of Life Index and ‏Psoriasis Area Severity Index‏. Data was analyzed using Pearson correlation coefficient, independent t-tests, one-way ANOVA, and linear regression analysis via SPSS v.21 at a significance level less than 0.05. Results: ‎The mean scores (standard deviation) of psoriasis severity and total quality of life were 14.26 (9.41) and 14.13 (6.47), respectively. There was a positive, strong, and significant relationship between psoriasis severity and total quality of life (r= 0.622, P < 0.0001). Psoriasis severity was found to be mostly associated with the dimensions of psoriasis effects on daily life activities, symptoms, and emotions, respectively. Conclusion: ‎As the results revealed, the higher the psoriasis severity indicated the lower the quality of life. This study showed the significance of addressing quality of life along with psoriasis severity in the process of assessing and treating patients. The results can serve as a foundation for interventional studies aiming at improving the quality of life in patients with psoriasis.